2022
DOI: 10.1007/s00403-022-02455-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of propolis for skin wound healing: systematic review and meta-analysis

Abstract: Propolis is a natural resin that is produced by bees. It has anti-in ammatory and antibiotic properties, promotes reepithelization, and stimulates skin regeneration. Propolis has great potential for the development of new therapeutic approaches to treat skin ulcers. The present study performed a systematic review and meta-analysis of published studies of the use of propolis for the regeneration of cutaneous wounds and its e cacy as a therapeutic agent. Data were collected from articles in the PubMed, SCOPUS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Recently, a systematic review and meta-analysis of more than 40 published studies found strong evidence that propolis is effective in the treatment of skin wounds, including difficult-to-heal ulcers found in patients with diabetes; in fact, propolis was shown to promote a higher percentage of healing than the interventions classically employed [25]. Another interesting aspect is that a large number of in vivo studies have combined propolis with other substances, such as honey, and different biomaterials (nanoparticles, nanofibrous, biocelullose membrane, hydrogel) to achieve additive or synergistic effects in the skin regeneration process [25,[57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a systematic review and meta-analysis of more than 40 published studies found strong evidence that propolis is effective in the treatment of skin wounds, including difficult-to-heal ulcers found in patients with diabetes; in fact, propolis was shown to promote a higher percentage of healing than the interventions classically employed [25]. Another interesting aspect is that a large number of in vivo studies have combined propolis with other substances, such as honey, and different biomaterials (nanoparticles, nanofibrous, biocelullose membrane, hydrogel) to achieve additive or synergistic effects in the skin regeneration process [25,[57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Given that wound healing is a complex event, in recent years, efforts have been made to discover a pro-healing agent that shortens the process, decreases cost, is easily available and has minimal side effects on the patient [7]. In this regard, propolis has been shown to be a promising alternative to promote tissue repair and has ideal therapeutic effects [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Another skin condition where great potential for DMG-Na could be realized is the management of wound healing. Indeed, we found that DMG-Na stimulates proliferation and migration of epidermal keratinocytes, key events of re-epithelization after wounding [65,66]. Further, we also showed that DMG-Na upregulates the synthesis and release of VEGF and GM-CSF, positive master regulators of skin wound healing [67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 64%
“…The wound healing process comprises hemostasis, inflammation, proliferation (re‐epithelialization), and remodeling (Li et al, 2017; Schultz et al, 2011). Propolis has been seen in several studies to help promote the re‐epithelialization of wounds (Gregory et al, 2002; Machado Velho et al, 2022; Olczyk, Komosinska‐Vassev, et al, 2013; Pessolato et al, 2011).…”
Section: Wound Healing Effects Of Propolismentioning
confidence: 99%